Rancang Bangun Alat Pengukur Detak Jantung Menggunakan Komunikasi Wifi dengan Android - Yulidarti Yulidarti; Hendri Hendri (JTEV (Jurnal Teknik Elektro dan Vokasional), 2020)
Health is a vital element in all activities carried out by humans. However, humans often do not understand the true meaning of physical health. Physically healthy means all body organs are in their actual size and are in optimal condition, and can function normally. Physically healthy is measured from the basic parameters of normal values of the body's vital signs, such as the heart. In this final project is designed to build a heart rate measuring device using WiFi communication with Android. This final project aims to determine the accuracy of the easy pulse sensor in detecting heartbeats on the fingers, which then the system will be used to record the patient's heart rate throughout the day on the move. This system is designed using an easy pulse sensor module which will be connected to the NodeMCU wifi ESP8266. Heart data is recorded or saved on android. The results of this measurement are compared with manual measurement and then as a reference for the level of accuracy using an omron brand heart rate meter. Testing of this tool is done by measuring the index finger with a tool made by the author and is done by pairing an omron wrist beat meter then the instrument that was attached was brought to the chest, this calculation is carried out for 60 seconds. This PDJ (Heart Rate Measurement) test is performed on male and female narcotics once on the index finger and wrist. Where random samples conducted for men and women have an error ratio of 0-6%.